A comparative study of cell proliferation markers in breast carcinomas. Issue 2 (April 1995) - Leong, A S-Y; Vinyuvat, S; Suthipintawong, C; Milios, J
Abstract : Aims —To investigate the tumour cell proliferative index obtained by immunostaining of paraffin wax sections of 30 cases of breast carcinoma with monoclonal antibodies MIB1, KiS1 and KiS5, and polyclonal Ki67 antisera to the Ki67 antigen and 19A2 and PC10 antibodies to proliferating cell nuclear antigen and the possible correlation between these indices and that of monoclonal Ki67 antibody in frozen sections of the same tumours. Methods —All tumour samples had been uniformly fixed and processed and sections were subjected to microwave antigen retrieval before immunostaining in all instances except for monoclonal Ki67 antibody which was used in cryostat sections. Tumour cell proliferative indices were evaluated by two independent examiners, each counting 500 tumour cells with the aid of a cross-hatched grid. Results —Proliferative indices obtained with MIB1, polyclonal Ki67, KiS1, and KiS5 correlated with those obtained with monoclonal Ki67 in frozen sections. Proliferative indices obtained with monoclonal 19A2 and PC10 showed no correlation with those of monoclonal Ki67 antibody. The staining obtained with MIB1 was the most intense and the easiest to read. Conclusions —Monoclonal antibodies MIB1, KiS1 and KiS5 and polyclonal Ki67 antiserum appear to be suitable substitutes for monoclonal antibody Ki67 in the assessment of tumour cell proliferative index. As these reagents are all immunoreactive in paraffin wax sections, they overcome the requirement for frozen tissue for immunostaining with monoclonal Ki67.